Cover: International Journal of Intelligent Systems, Volume 36 Issue 5 May 2021. Issue 5 (May 2021) - Kwon, Hyukwon; Oh, Kwang Cheol; Choi, Yeongryeol; Chung, Yongchul G.; Kim, Junghwan
Abstract : Cover Caption : The cover image is based on the Research Article Development and application of machine learning‐based prediction model for distillation column by Hyukwon Kwon et al., https://doi.org/10.1002/int.22368 .